Kitagadottak . Disowned - Kőszegi, Edit; Szuhay, Péter (Forum Film, 2000)
Verzio FF The story of an extended (mostly Roma) family living in Northern Hungary, near the Slovak border. The starting-point of the family story is an old photo which suggests that they might have been of aristocratic origin. Following the different branches of the family tree, searching for ancestors together with the characters, the filmmakers interview family members leading different ways of life, as the family includes miners, musicians and farmers. This social and cultural 'in-betweenness' determines their life: where do they belong, with whom they can identify, what family stories will they pass on to the next generations?